Woodchip-filled trenches: A solution to enhance urban water infiltration capacity? - P. Louis; L. Delgado-Gonzalez; L. Lassabatère; S. Czarnes; J. Aubert; A. Imig; R. Clément (Geoderma)
Urban water management has been increasingly relying on infiltration to limit the environmental impact of stormwater, secondary treated effluent and gray water. The infiltration systems used are generally based on non-renewable drainage materials featuring a pronounced ecological footprint (i.e., excavation and transport), such as gravel. This paper investigates the possibility of using woodchips instead of traditional drainage materials. Our study examines flow dynamics in woodchip-filled infiltration trenches at four decentralized gray water sites, on a silty clay soil. Infiltration tests were conducted using the Beerkan method to measure soil infiltration capacity both beneath the woodchip-filled trenches and in adjacent soil. Soil hydraulic functions were determined according to the BEST method, then comparisons were drawn between the woodchip-filled trench and natural soil. Results indicate that woodchips locally maintain or enhance soil infiltration rates, with a hydraulic conductivity up to 200 times higher in woodchip-treated soil. Additional soil measurements and analyses serve to formulate hypotheses on how the woodchips actually contribute to these effects. Dye tracer experiments revealed preferential pathways facilitated by macro fauna (earthworms) and, most likely, plant roots. This last information input has been corroborated since earthworm counts did prove to be significantly higher in the woodchips than in the soil. A chemical analysis of the soils also showed a significant enrichment of carbon and nitrogen under the trench, which may also improve soil structure and stability and perhaps indirectly enhance water infiltration capacity. In summary, the presence of woodchips in infiltration trenches improves the soil hydraulic conductivity at saturation for systems that have been in use for 5 to 10 years. These findings underscore the potential of woodchips in sustainable urban water management in order to enhance the functionality and efficiency of drainage materials by means of limiting the clogging effect.